Universiti Putra Malaysia Clinched 6th Spot in Greenmetric World University Ranking - Universiti Putra Malaysia, Bahagian Komunikasi Korporat (2010)
SERDANG, January 3rd - Universiti Putra Malaysia clinched the 6th spot with total points of 7,698.60 in the UI Greenmetric World University Ranking making it the only Malaysian university in the top 10 of the esteemed listing.